2015
DOI: 10.1172/jci77139
|View full text |Cite
|
Sign up to set email alerts
|

Defective glycosylation of coagulation factor XII underlies hereditary angioedema type III

Abstract: Hereditary angioedema type III (HAEIII) is a rare inherited swelling disorder that is associated with point mutations in the gene encoding the plasma protease factor XII (FXII). Here, we demonstrate that HAEIII-associated mutant FXII, derived either from HAEIII patients or recombinantly produced, is defective in mucin-type Thr309-linked glycosylation. Loss of glycosylation led to increased contact-mediated autoactivation of zymogen FXII, resulting in excessive activation of the bradykinin-forming kallikrein-ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(114 citation statements)
references
References 77 publications
1
109
0
4
Order By: Relevance
“…C1-INH deficiency leads to angioedema because it controls contact system activation; in the absence of C1-INH, the contact system releases bradykinin to cause angioedema. Recent evidence supports the notion that F12 mutations also facilitate release of BK [42]. For U-HAE, the mechanism of angioedema formation remains unclear, and no significant data have been reported.…”
Section: Hereditary Angioedemamentioning
confidence: 79%
“…C1-INH deficiency leads to angioedema because it controls contact system activation; in the absence of C1-INH, the contact system releases bradykinin to cause angioedema. Recent evidence supports the notion that F12 mutations also facilitate release of BK [42]. For U-HAE, the mechanism of angioedema formation remains unclear, and no significant data have been reported.…”
Section: Hereditary Angioedemamentioning
confidence: 79%
“…We hypothesized that low FXII reduces kallikrein formation and consequently the release of bradykinin, which hinders formation of edema (opposite of hereditary angioedema type III, in which a gain of function in FXII induces formation of edema). 32 In thrombotic mice with low FXII, impaired edema formation would worsen the phenotypic response through an inability to manage intravenous pressure after thrombotic occlusion. Quantitation of edema in the head (measured by the thickness of the edemic dermis in coronal sections of the head) did not provide any information regarding low FXII-altered edema formation (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of coagulation factor X (FX) by Russell's viper venom and Xase is altered in the presence of O-glycans, 22 as is the sensitivity of coagulation factor XII (FXII) to contact activation, with loss of FXII O-glycans recently implicated in the pathogenesis of hereditary angioedema. 23 Furthermore, murine studies have shown that O-glycans are important for the hemostatic process in vivo, because truncation of O-glycans results in severe bleeding deficits, aberrant angiogenesis, and platelet biogenesis, whereas loss of specific O-glycan sites leads to increased bleeding time and VWF insufficiency. [24][25][26] These examples suggest important functions of O-glycosylation, yet, primarily because of technical limitations, we have little information on where the O-glycans are localized.…”
Section: Introductionmentioning
confidence: 99%